From Kafka to Sebald : modernism and narrative form - Wilke, Sabine, 1957- (New directions in German studies ;, 2012)
"This volume is a response to a renewed interest in narrative form in contemporary literary studies, taking up the question of literary narratives and their encounters with modernism and postmodernism within the German-language milieu. Original essays written by scholars of German and Comparative Literature approach the issue of narrative form anew, analyzing the ways in which modernist and postmodernist German-language narratives frame and/or deconstruct historical narratives. Beginning with the German-language modernist author par excellence, Franz Kafka, the volume's essays explore the unique perspective on historical change offered by literature. The authors (Kafka, Kappacher, Goll, Bernhard, Menasse, and Wolf, among others) and works interpreted in the essays included here span the period from before World War I to the post-Holocaust, post-Wall present. Individual essays focus on modernism, postmodernism, narrative theory, and autobiography."--Opening screen of ebook's web page (EBL platform, October 9, 2013)